Edaphic characteristics of Quercus suber woods in Latium (Rendiconti Lincei, 1997)
{In this paper the results are reported of a soil survey done in selected sites of Latium un- der the most significant Quercus suber woods (Cytiso-Quercetum suberis Testi, Pignatti and Lucattini 1994) previously studied from a phytosociologicat point of view. After describing the dominant soil type of each area, physical-chemical characteristics have been analysed in order to point out the significance of edaphic factors in the distribution and floristic composition, of the Quereus suber co,noses. Bioclimatic, structural and edaphic features of this vegetation showed a great convergence; among all the parameters examined, AWC resulted to be the most effective one in conditioning the mesophilous character of Quercus suber coenoses growing in Latium. In this respect this type of vegetation shows rather strong affinities with mixed Quercztr cerrz} woods, both in the floristic composition and in the edaphic requirements, as already suggest- ed in the most recent phytosociological studies.